Genome analysis of Lachnoclostridium phocaeense isolated from a patient after kidney transplantation in Marseille. (May 2021) - Dandachi, I.; Anani, H.; Hadjadj, L.; Brahimi, S.; Lagier, J.-C.; Daoud, Z.; Rolain, J.-M.
Abstract: Lachnoclostridium phocaeense is a new species in the genus Lachnoclostridium . Lachnoclostridium phocaeense is a Gram-positive anaerobic rod. This strain, Marseille-P3177 T (CSUR = P3177) with the below described genome was isolated from the urine sample of a women after kidney transplantation. The strain genome is 3 500 754 bp long with 50.62% G + C content and consists of a single contig (GenBank accession number NZ_LT635479.1).